MORBIDITY AND PREVALENCE OF THE NERVOUS SYSTEM DISEASES IN CHILDREN OF UKRAINE - Volosovets, O.P.; Kryuchko, T.O.; Kryvopustov, S.P.; Gonchar М.О.; Volosovets, A.O.; Stetsyuk, R.A.; Loginova, I.O.; Khomenko, V.E.; Shcherbynska, K.M.; Verbytskyi, I.V. (World of Medicine and Biology, 2020)
The article presents clinical and epidemiological data on the prevalence and incidence of the nervous system diseases (hereinafter  NSD) in all regions of Ukraine from 1993 to 2019. The incidence rates of NSD in children from regions with radiological control areas were higher than the nation-wide ones and the incidence rates in children from other regions by 15.9%. The incidence of NSD in children affected by the Chernobyl accident was higher than the nation-wide by 44.5%, which does not permit to exclude the direct and indirect effects of radiation. The results of our observations on the incidence of the NSD in children of Ukraine indicate that children suffered prolonged exposure to ecotoxic factors, including radiation, have higher levels of prevalence and morbidity of the NSD, which requires specialists’ attention and effective medical and diagnostic measures.